Cumulative Lifetime Burden of Cardiovascular Disease From Early Exposure to Air Pollution - Kim, Juyong Brian; Prunicki, Mary; Haddad, Francois; Dant, Christopher; Sampath, Vanitha; Patel, Rushali; Smith, Eric; Akdis, Cezmi; Balmes, John; Snyder, Michael P.; Wu, Joseph C.; Nadeau, Kari C. (Journal of the American Heart Association, 2020)
The disease burden associated with air pollution continues to grow. The World Health Organization (WHO) estimates ≈7 million people worldwide die yearly from exposure to polluted air, half of which—3.3 million—are attributable to cardiovascular disease (CVD), greater than from major modifiable CVD risks including smoking, hypertension, hyperlipidemia, and diabetes mellitus. This serious and growing health threat is attributed to increasing urbanization of the world's populations with consequent exposure to polluted air. Especially vulnerable are the elderly, patients with pre‐existing CVD, and children. The cumulative lifetime burden in children is particularly of concern because their rapidly developing cardiopulmonary systems are more susceptible to damage and they spend more time outdoors and therefore inhale more pollutants. World Health Organization estimates that 93% of the world's children aged <15 years—1.8 billion children—breathe air that puts their health and development at risk. Here, we present growing scientific evidence, including from our own group, that chronic exposure to air pollution early in life is directly linked to development of major CVD risks, including obesity, hypertension, and metabolic disorders. In this review, we surveyed the literature for current knowledge of how pollution exposure early in life adversely impacts cardiovascular phenotypes, and lay the foundation for early intervention and other strategies that can help prevent this damage. We also discuss the need for better guidelines and additional research to validate exposure metrics and interventions that will ultimately help healthcare providers reduce the growing burden of CVD from pollution.